Optimalisasi Pendapatan Dalam Kombinasi Pengelolaan Hutan Tanaman Di Provinsi Kalimantan Timur - Mohammad Wahyu Agung; Maya Preva Biantary (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
This research was conducted at the village of Sukamaju in Kutai Kartanegara Regency, PT Melapi Timber and PT INHUTANI I Long Well, which includes observation, the conduct of research and data collection. The object of this study was people or companies that commercialize three plants of Mahogany (Swietenia macrophylla), Red Meranti (Shorea leprosula) and Parica (Schizolobium amazonicum) of various ages (4, 8, 15 and 17 years).Analysis of the data include: Analysis of Linear Programming and SWOT analysis. Results of the research showed that: (1) The optimal revenue of forest plantation industry is Rp2.739.503.000,-, this means that if the head of the family has a land area of 15 ha, the income per month is Rp4.082.469,- or Rp204.123,- per hectare. (2) An optimal income of forest plantation industry achieved with the combination of Red Meranti plants 5 ha, Parica 5 ha and Mahogany 5 ha, means that each family has a land area of 15 ha. (3) The remaining input supply all used up. (4) An income sensitivity interval shows that the optimal reception will not change if the increase or decrease in receipts of Red Meranti, Parica and Mahogany happened to the limit specified intervals, increase or decrease the income is influenced by the price of timber in the market (5) Cost of production used to achieve optimal revenue amounted Rp790.997.000,-. Production costs in the construction of HTR ranges between 40-60 million IDR per hectare, whereas the standards costs set by the government is smaller at only 9-12 million IDR per hektar. (6) Sensitivity interval of input supplies of manure, harvesting and thinning, and (7) From the SWOT analysis: the things to be done by the stakeholders are working together to minimize the weaknesses that exist and to face the threat, in addition also to manage the power to increase the opportunities.